2019
DOI: 10.1080/14786419.2018.1557656
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.)

Abstract: Volatile oil composition of leaves and fruits of Terminalia arjuna (Roxb.) was reported for the first time. Oils were extracted by microwave assisted hydrodistillation where yield of both oils were found to be 0.20% and their GC-MS analyses led to the identification of 65 and 48 constituents, respectively. Major constituents of leaves were carvacrol (11.17%), thymol (6.52%), α-terpinyl acetate (5.92%) and anethole (5.13%) while that of fruits were (E)-jsoeugenol (11.48%), furfural (8.25%), p-vinylguaiacol (6.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These MDR strains were also inhibited by essential oils of Eucalyptus globulus and Thymus vulgaris with MIC values of 85.6 (µg/mL) and 18.5 (µg/mL) against MRSA respectively [11,12]. Strong inhibitory activity was observed by the essential oils of Clerodendrum serratum against MRSA whereas fruit oil of a common Sub-continent tree, Terminalia arjuna exhibited an MIC 0.16 mg/mL against MRSA [13,14]. Several other plants have been checked for their antibacterial potential against MRSA among which the most active essential oils include Cinnamomum verum, Satureja montana, Origanum heracleoticum, Cinnamomum cassia and Corydothymus capitatus.…”
Section: Discussionmentioning
confidence: 98%
“…These MDR strains were also inhibited by essential oils of Eucalyptus globulus and Thymus vulgaris with MIC values of 85.6 (µg/mL) and 18.5 (µg/mL) against MRSA respectively [11,12]. Strong inhibitory activity was observed by the essential oils of Clerodendrum serratum against MRSA whereas fruit oil of a common Sub-continent tree, Terminalia arjuna exhibited an MIC 0.16 mg/mL against MRSA [13,14]. Several other plants have been checked for their antibacterial potential against MRSA among which the most active essential oils include Cinnamomum verum, Satureja montana, Origanum heracleoticum, Cinnamomum cassia and Corydothymus capitatus.…”
Section: Discussionmentioning
confidence: 98%
“…Because of fertile lands, these countries have diversity in plants of medicinal importance, and a variety of medicinal plants are grown and harvested. Although, many plants have been studied, however, there are numerous other plants either uninvestigated or have rare literature on them, and hence, there is a great need to explore their essential oil composition and medicinal properties especially antimicrobial activity [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most popular species includes J. chinensis , J. excelsa , and J. communis . Research studies of the various species of Juniperus tree revealed a wide range of unique medicinal properties such as antimicrobial [ 1 ], anticancer [ 2 ] antioxidant [ 3 ], antitumor [ 4 ], antidiabetic [ 5 ], antimicrobial [ 6 ], and many other therapeutic properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%